Blast actions in aircrafts: An integrated methodology for designing protection devices. (15th November 2018) - Masi, Filippo; Mariano, Paolo Maria; Vannucci, Paolo
Highlights: We provide non-standard integrated methodology to investigate the effects of internal blast actions on aircrafts. We design new protection devices: composite structures. We consider external actions arising at cruising altitude. Our methodology can be used in general for different structures. Abstract: We introduce a numerical approach for evaluating the behaviour of aircraft fuselages subjected to internal explosions. At variance with available approaches, we consider fluid-structure interactions through a novel integrated methodology able to take into account both stress at cruise altitude and blast fast-dynamics in interaction with pressurization not considered as a static load. The precision of the proposed numerical procedure allows us to foresee a nonstandard composite protective device.